Conscription, Conscience and Controversy: The Friends' Ambulance Unit and the 'Middle Course' in the First World War. Issue 2 (December 2016) - Wynter, Rebecca
Abstract : The Friends' Ambulance Unit (FAU) was established by British Quakers outside the formal structures of the Religious Society of Friends in August 1914 to provide frontline voluntary medical aid in Belgium. It was headed by a London-based 'Committee of the Friends' Ambulance Unit' (FAU Committee), which included men at the heart of the nation's political elite. This article considers the FAU Committee's response to the threat and enactment of conscription, and in turn what this did to the Unit's internal workings, its personnel and their consciences, centring on the experiences of four members of its 'Foreign Section' in France and Belgium. In doing so, it not only reveals for the first time the negotiations between FAU Committee members and Government representatives, but also suggests that the 'middle course' steered between prison and the military was, if not always popular, successful in ensuring the continuation of aid work and creating a space for consciences of many hues.